STUDY ON PERTAMAX SUPER HEATED STEAM AS AN ADDITIVE TO IMPROVE MOTORCYCLE ENGINE PERFORMANCE - prasetyo, andi (TRAKSI, 2024)
Engine performance indicators, especially motorcycle engines, are the amount of power, torque and fuel efficiency. To determine the performance of power and torque, the equipment used is a dynotest tool. This study takes the theme of the use of additives as additives in fuel. The additive is in the form of Pertamax vapor which is heated and distributed to the manifold.The purpose of this study was to examine the performance of power and torque on a motorcycle engine. The research method with the addition of additives in the form of pertamax steam heated with variable fuel consumption, namely pertalite, pertalite plus Pertamax steam and Pertalite plus heated Pertamax steam. The results of this study show that the maximum torque of Pertalite is 9.11 Nm, Pertalite + Pertamax Steam has a maximum torque of 8.93 Nm and Pertalite + Pertamax Steam + Heater has a maximum torque of 8.84 Nm. The maximum power on Pertalite is 7.6 HP, on Pertalite + Pertamax Steam the power is 7.7 HP and Pertalite + Pertamax Steam + Heater is 7.7 HP.